Penerapan Metode VIKOR Dalam Menentukan Aplikasi Belanja Online Terbaik Berdasarkan Konsumen - Rika Setiana; Widya Try Taradipa; Agus Perdana Windarto (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2022)
People's lives are becoming more instantaneous as technology advances, and many people have a lot of freedom in their daily activities. This means that people need comfortable goods to meet their daily needs. A marketplace is a type of media that serves as a place for sellers and buyers to do business and trade. People buy things online a lot these days, but a lot of them don't know how to choose an online marketplace, so the authors decided to do some research on how to choose the best online shopping app so that people can easily figure out which app to use and won't be disappointed in the future. So, it's important to figure out which is the best online shopping app. This study uses the VIKOR method to make a decision-making system. In this study, the authors started by doing surveys. They chose a data collection method based on a questionnaire or a Google form questionnaire. Based on how the VIKOR method was used in this study, the best marketplace that can be used is Shoope. With this research, it is hoped that the public will be able to find out how to choose the best app for shopping online.